Caltural landscap’s changes of Solyna commune - Ihor Kozak; Hanna Kozak (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The main aim of the present work was to analyze the dynamics of settlements from the 2nd half of the 18th century to 2nd half of 20th century in Solyna commune (in polish Solina), in Lesko district, Podkarpackie voivodeship in Eastern Poland. There was analyzed the Solyna commune in terms of the changes of settlements and applied maps together with published historical data for the analysis of changes in its structure. The first was the historical map, in other words the tactical map of «WIG- Military Institute of Geography». Next maps from the «WMS-Web Map Service, Geoportal» were analyzed. Changes in the number of villages and households population dynamics for Greek-catholics, «Latynnykys» and Jews for the year 1785 were evaluated applying ArcGIS 10.3 program. Ukrainian ones were evaluated using ArcGIS program in comparison with the number of Poles and Jews for the year 1939. Ethnic and religious composition from the 2nd half of the 18th century to 2nd half of 20th century and the character of settlements distribution in Solyna commune was evaluated based on the study of spatial distribution of settlements with the use of Spatial Statistics (Spatial Autocorrelation Global Moran's test, Standard Deviational Ellipse and Mean Centre). In 1785 there were 80,55% of Greek-catholics and in 1939 there were 89,82% of Ukrainians in Solyna commune. There was confirmed a similar configuration of Standard Deviation Ellipse and Mean Center for Greek-catholic for the year 1785 and Ukrainians for the year 1939 in Solyna commune. The scale and results of such changes are essential for future research, mainly in terms of the change of traditional village system infrastructure and culture.